The The Years Of Schooling Contribution As Factors That Most Considered In Increasing Human Development Index - Listiyani, Nurul; Zulfikar , Rizka; Jaelani, Achmad; Susanto, Didi (CV. Inara, 2022)
Banjar Regency as one of the second-level regions in South Kalimantan Province has an HDI value that always experiences growth and is included in the medium category. However, if we look at the average growth rate of HDI value (shortfall reduction) during this period, it is included in the low category, which is around 0.74 percent (2010-2021 period) and only ranks 11th out of 13 districts. This shows that development programs in Banjar Regency, although they have a positive impact on improving the quality of life of the population, are not large enough when compared to development programs that have been carried out by other regencies/cities.To be able to improve these conditions, of course, it is necessary to study the causes of the low rate of growth of the HDI in Banjar Regency on the three basic dimensions of forming the HDI, namely the Dimensions of Health, Dimensions of Education and Dimensions of Decent Living Standards. Where the health dimension is represented by life expectancy (AHH), the education dimension is represented by the Average Years of Schooling (RLS) and Expected Years of Schooling (HLS), and the dimension of Decent Living Standards is represented by the Adjusted Expenditure Figures (APP).The method used is descriptive quantitativequalitative, using the Partial Least Of Square (PLS) technique to determine the influence of the dimension indicators forming HDI. The results of this research are as follows: (1) Life Expectancy and Average Years of Schooling have no significant effect on the HDI Figures of Kab. Banjar, (2) Expected Years of Schooling and Adjusted Per capita Figures have a significant effect on HDI figures, (3) indicators forming HDI such as AHH, RLS, HSL and APP together have a significant effect on HDI Kab. Banjar because the significance value is (0.000) < 0.05. With a coefficient of determination (R Squared Change) of 1,000, it can be said that the variance of the HDI value is 100% influenced by the forming indicators and is not influenced by indicators other than the indicators forming the HDI, (4) The order of indicators that contribute the most to the HDI Regency. Banjar from the largest are: Expected Length of Schooling, Life Expectancy, Expenditure Per Capita and Average Length of Schooling. In this case it can be said that the attention of the district government. Banjar during the period 2010-2021 focused more on HLS, AHH and APP indicators than on RLS indicators (the indicator with the smallest contribution).